Achieving a table-like magnetocaloric effect and large refrigerant capacity in in situ multiphase Gd65Mn25Si10 alloys obtained by crystallization treatment. (20th December 2016) - Shen, X Y; Zhong, X C; Huang, X W; Mo, H Y; Feng, X L; Liu, Z W; Jiao, D L
Abstract: In situ multiphase structure Gd65 Mn25 Si10 alloys were fabricated by melt spinning and subsequent crystallization treatment. In the process of crystallization, the α -Gd, GdMn2 and Gd5 Si3 phases precipitate in the amorphous matrix in turn. The Curie temperature ( T C ) values for the α -Gd crystallization phase and amorphous matrix can be tailored by tuning the crystallization treatment time. All three multiphase alloys obtained by crystallization treatment at 637 K for 20, 30 and 40 min, respectively, undergo multiple successive magnetic phase transitions. A table-like magnetic entropy change over a wide temperature range (~90–120 K) and a large full width at half maximum (Δ T FWHM ) magnetic entropy change (~230 K) were achieved in the above-mentioned crystallized alloys, resulting in large refrigerant capacities (RCs). The enhanced RCs of the three crystallized alloys for a magnetic field change of 0–5 T are in the range of 541–614 J kg −1 . Large Δ T FWHM and RC values and a table-like (−Δ S M ) max feature obtained in in situ multiphase Gd65 Mn25 Si10 crystallized alloys make them suitable for potential application in efficient Ericsson-cycle magnetic refrigeration working in a temperature range from 74 to 310 K.